2020
DOI: 10.1051/0004-6361/202039061
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven approach to constraining the atmospheric temperature structure of the ultra-hot Jupiter KELT-9b

Abstract: Context. Observationally constraining the atmospheric temperature-pressure (TP) profile of exoplanets is an important step forward for improving planetary atmosphere models, thus further enabling one to place the detection of spectral features and the measurement of atomic and molecular abundances through transmission and emission spectroscopy on solid ground. Aims. The aim is to constrain the TP profile of the ultra-hot Jupiter KELT-9b by fitting synthetic spectra to the observed Hα and Hβ lines and identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 85 publications
(209 reference statements)
2
50
1
Order By: Relevance
“…The pretabulated cross 1 http://kurucz.harvard.edu/linelists/gfall/ sections of these molecules were taken from the public opacity database for exoplanetary atmospheres 2 . We also extended continuum opacity sources by including, for example, continuum transitions of H − , He − , and metals (see Fossati et al 2020Fossati et al , 2021. The HELIOS calculations were performed assuming local thermodynamic equilibrium.…”
Section: Comparison With Self-consistent Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pretabulated cross 1 http://kurucz.harvard.edu/linelists/gfall/ sections of these molecules were taken from the public opacity database for exoplanetary atmospheres 2 . We also extended continuum opacity sources by including, for example, continuum transitions of H − , He − , and metals (see Fossati et al 2020Fossati et al , 2021. The HELIOS calculations were performed assuming local thermodynamic equilibrium.…”
Section: Comparison With Self-consistent Modelsmentioning
confidence: 99%
“…Ultra-hot Jupiters (UHJs) are giant exoplanets with very high dayside temperatures that typically exceed 2000 K. Theoreti-cal studies suggest that their properties are different from those of planets with more modest temperatures. For example, their dayside atmospheres can be dominated by atoms and ions with a large number of molecules that are thermally dissociated (e.g., Lothringer et al 2018;Parmentier et al 2018;Kitzmann et al 2018;Fossati et al 2020). These planets have ex-treme differences in their dayside to nightside temperature and are also different chemically (e.g., Bell & Cowan 2018;Komacek & Tan 2018;Tan & Komacek 2019;Helling et al 2019;Molaverdikhani et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wyttenbach et al 2020). Fossati et al (2020) discuss the differences in the Hα and Hβ lines as observed by different groups with different instruments and different reduction pipelines. Employing non-LTE radiative transfer, a temperature of 10 4 .…”
Section: Introductionmentioning
confidence: 98%
“…It is subject to intense irradiation from the star and extreme atmospheric escape due to its large extended hydrogen envelope reaching the Roche-Lobe limit (Yan & Henning 2018;Wyttenbach et al 2020). Measurements of the neutral iron line by Pino et al (2020) imply the presence of a thermal inversion, as does modeling by Fossati et al (2020).…”
Section: Introductionmentioning
confidence: 99%